The Brazilian Video Marketplace: A Regulatory Analysis and Perspective under the US Law - Pinheiro, Guilherme Pereira (Law, State and Telecommunications Review, 2011)
This work investigates the arising regulatory framework of electronic content distribution within the Brazilian Telecommunications Industry. The article describes the current stage of the convergence revolution in the world from diverse perspectives and how the rigidity of the classical definitions and the regulatory framework of traditional telecommunications services have delayed and even endangered the advance of convergence tools in Brazil. In the context of the convergence revolution, special attention is paid to disputes between Brazilian broadcasters and Internet-based content providers and how the emerging legislation will affect them. Finally, from the current status questionis of the debate in Brazil, the paper analyzes the proposals and consequences of the electronic content control regulations in the country. This article constantly compares the Brazilian regulatory background with that of the United States for referential and critical analysis purposes.